Pengembangan Masterplan Kawasan Wisata Desa Kebobang Berbasis Business-Tourism - R. Machmud Sugandi; Mohammad Musthofa Al Ansyorie; M. Aris Ichwanto (Jurnal Ekonomi, Bisnis dan Pendidikan (JEBP), 2023)
Abstract Kebobang Village is in a mountainous area, so it has various potential. The many plantation, agricultural, and forestry potentials owned by Kebobang Village can be an opportunity for Kebobang Village to be developed into a rural tourist destination. The tourist destinations will be combined with the development of rest areas so that later, they can become a place for tourists to stop by to rest while enjoying the village views. It is hoped that developing tourist destinations properly and optimally will improve the economy of rural communities and reduce the number of unemployed by absorbing many workers. The development of tourist destinations also requires promotional media in the form of a business-tourism-based masterplan. Due to the unavailability of a masterplan or business-tourism-based layout design in the Kebobang Village tourist area, it is necessary to have a touch and application of science and technology to create a masterplan or business-tourism based layout design in the Kebobang Village-tourist-area. Abstrak Desa Kebobang merupakan desa yang berada di daerah pegunungan sehingga membuatnya memiliki beragam potensi. Banyaknya potensi perkebunan, pertanian, serta kehutanan yang dimiliki oleh Desa Kebobang dapat menjadi peluang bagi Desa Kebobang untuk dikembangkan menjadi destinasi wisata pedesaan. Destinasi wisata yang dikembangkan akan dipadukan dengan pengembangan rest area, sehingga nantinya hal ini dapat menjadi tempat bagi wisatawan singgah untuk beristirahat sembari menikmati pemandangan desa. Pengembangan destinasi wisata secara baik dan maksimal diharapkan akan dapat meningkatkan perekonomian masyarakat desa dan mengurangi jumlah pengangguran dengan terserapnya banyak tenaga kerja. Pengembangan destinasi wisata juga memerlukan adanya media promosi berupa masterplan berbasis business-tourism. Berhubung belum tersedianya suatu masterplan atau desain layout berbasis business-tourism pada kawasan wisata Desa Kebobang, maka diperlukan adanya sentuhan dan aplikasi IPTEKS untuk keperluan pembuatan masterplan atau desain layout berbasis business-tourism kawasan wisata Desa Kebobang.